Exploring the meaning of life : an anthology and guide - Seachris, Joshua W. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2013)
"Much more than just an anthology, this survey of humanity's search for the meaning of life includes the latest contributions to the debate, a judicious selection of key canonical essays, and insightful commentary by internationally respected philosophers"--
Includes bibliographical references and index.
Keywords: Livets mening; Mening (filosofi); Life; Meaning (Philosophy); Life -- Religious aspects; PHILOSOPHY / Movements / Existentialism; Meaning (Philosophy); Meaning (Philosophy); Meaning (Psychology); Life